1999
DOI: 10.1053/joca.1998.0242
|View full text |Cite
|
Sign up to set email alerts
|

Joint distraction in treatment of osteoarthritis: a two-year follow-up of the ankle

Abstract: Results of the present prospective study confirm the findings of the previous retrospective study and suggest that Ilizarov joint distraction is a promising treatment for severe ankle OA, at least delaying the need for a joint fusion. Considering the high prevalence of OA and the lack of a remedy for this disorder, Ilizarov joint distraction as a treatment for OA may have great medical, social and economic impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
96
2
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(101 citation statements)
references
References 9 publications
2
96
2
1
Order By: Relevance
“…In a prospective, uncontrolled study of 15 patients, we showed that joint distraction for the treatment of severe ankle OA resulted in significant relief of pain after 1 year, with further improvement during the following year. Function and clinical status also improved after 1 year and further improved during the following year (19).…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…In a prospective, uncontrolled study of 15 patients, we showed that joint distraction for the treatment of severe ankle OA resulted in significant relief of pain after 1 year, with further improvement during the following year. Function and clinical status also improved after 1 year and further improved during the following year (19).…”
mentioning
confidence: 80%
“…Loss of function was measured using a slight modification of the score described by Van Valburg et al (19), based on the functional index for hip and knee OA (21); the maximum score for this measure is 30 ( Table 1). The clinical condition of the patients was measured by assessment of 4 features (maximum score 8) ( Table 1).…”
Section: Treatmentmentioning
confidence: 99%
“…Those investigators then performed a prospective series and found that more than two-thirds of patients demonstrated significant improvement at two years 36 . When that cohort was followed to an average of ten years (minimum, seven years), 73% of the patients reported good results 37 .…”
mentioning
confidence: 99%
“…13 Contraindications to this surgery include significant bone loss, active infection, significant boney deformity, and severe arthrosis. 13,34 Early clinical studies appear promising in decreasing pain and improving function, 55,68,90,91 especially in individuals younger than 45 years of age. 5 Complications such as painful toe flexion contractures and joint stiffness can result if the joint is excessively distracted.…”
Section: Distraction Arthroplastymentioning
confidence: 99%